81.7k views
5 votes
Problem #7 PLEASE HELP ;(

Is 6(x+0.4) equivalent to 3(2x+0.8)? YES or NO???????


Show your work!
6(x+0.4) 3(2x+0.8)

User Qdot
by
4.7k points

1 Answer

3 votes

Answer:

Yes

6(x+0.4) is equivalent to 3(2x+0.8)

Explanation:

Given in the questions two expressions

6(x + 0.4)

3(2x + 0.8)

We will apply distributive law

It is a law relating the operations of multiplication and addition, stated symbolically

a(b + c) = ab + ac

6(x + 0.4)

= 6(x) + 6(0.4)

= 6x + 2.4

3(2x + 0.8)

= 3(2x) + 3(0.8)

= 6x + 2.4

Since both equations when expanded have same answers, hence they are equivalent

User Yuriy Rozhovetskiy
by
5.2k points